2017
DOI: 10.1177/0363546517713164
|View full text |Cite
|
Sign up to set email alerts
|

Autograft Versus Allograft for Posterior Cruciate Ligament Reconstruction: An Updated Systematic Review and Meta-analysis

Abstract: Patients undergoing primary PCLR with either autograft or allograft can be expected to experience improvement in clinical outcomes. Autograft patients experienced less AP knee laxity postoperatively, although the clinical significance of this is unclear and subjective outcomes improved substantially and to a similar degree in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…A retrospective study conducted by Chahla et al [15] in 2017 indicated that the employment of the double-bundle technique for autograft and allograft resulted in an average posterior tibial translation of 2.4 and 4.9 mm. Belk et al [16] noted in a review published in 2017 that the anteroposterior laxities of the studied autograft group and the allograft group were 3.1 mm and 3.8 mm, respectively. A retrospective study conducted by Xu et al [17] in 2014 indicated that both the SSD of autograft and LARS were 3.3 mm.…”
Section: Discussionmentioning
confidence: 94%
“…A retrospective study conducted by Chahla et al [15] in 2017 indicated that the employment of the double-bundle technique for autograft and allograft resulted in an average posterior tibial translation of 2.4 and 4.9 mm. Belk et al [16] noted in a review published in 2017 that the anteroposterior laxities of the studied autograft group and the allograft group were 3.1 mm and 3.8 mm, respectively. A retrospective study conducted by Xu et al [17] in 2014 indicated that both the SSD of autograft and LARS were 3.3 mm.…”
Section: Discussionmentioning
confidence: 94%
“…The current knowledge in the use of allograft and autograft is that studies verify different outcomes dependent on location. In the cranioplasties, allograft has been shown to be superior [25]; in anterior crucial ligament (ACL), autograft showed better effect on bone formation [26], whereas in the posterior crucial ligament (PCL), the results are equal between the 2 grafts [27,28]. Hence, when comparing results for clinical implementation, using the correct graft is essential for the correct comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple techniques have been described in the literature for the operative management of patients with injuries to the PCL. 1 , 2 , 6 , 7 , 8 Historically, primary PCL repair was the preferred option; however, PCL reconstruction procedures are currently the most widely used option.…”
Section: Discussionmentioning
confidence: 99%
“…Belk et al. 2 published a systematic review and meta-analysis of 5 studies with 132 patients performed to compare PCL reconstruction with allograft versus autograft. They reported improved clinical outcomes in both groups but no differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation